Continuous genetic algorithm for grasping an object of a priori unknown shape by a robotic manipulator - A. D. Voronkov; S. A.K. Diane (Российский технологический журнал, 2023)
Objectives. The problem of providing the interaction of a robotic manipulator with a priori unknown objects in a given workspace is of great interest both to the research community and many industries. By developing a solution to this problem, it will be possible to reduce the time taken for robots to adapt to new environments and objects therein. One of the primary stages of providing the interaction of the robotic manipulator with objects is the search for the target position of the robot gripper based on the onboard sensor subsystem, which can be carried out by a number of methods. Methods associated with machine learning and self-learning technologies may not be suitable for some applications (for example, during rescue operations) when it is necessary to quickly search for the target position of the gripper for an a priori unknown object, about which there is no relevant information in the robot database. Therefore, for this problem, heuristic approaches – for example, genetic algorithms – seem to be applicable. The objectives of this work are to implement a search based on a continuous genetic algorithm for the target position of the robot gripper including collision avoidance and study its performance under virtual simulation.Methods. A heuristic search algorithm (continuous genetic algorithm) is used. The complex scene analysis algorithm uses classical image processing methods. In order to evaluate the effectiveness of the algorithm, virtual simulation is used.Results. The possibility of using a continuous genetic algorithm is analyzed in the problem of grasping an object of an a priori unknown shape avoiding collisions with other objects of a static scene. A complex scene analysis algorithm and implementation of a continuous genetic algorithm are presented for finding the target position of the gripper of a Kuka LBR iiwa 7 R800 robotic control system with redundant kinematics. The results of an experimental virtual simulation of the obtained algorithm are presented.Conclusions. The conducted research demonstrates the effectiveness of the continuous genetic algorithm in obtaining the target position of the gripper of the robotic manipulator under conditions when the static scene represents randomly located objects of various shapes.